PELATIHAN PEMANFAATAN TEKNOLOGI DIGITAL DALAM VISUALISASI DATA STATISTIK UNTUK KALANGAN PEMULA DI KABUPATEN MERANGIN - Leti Gustiana; Hidayati Rais; Muhammad Jainuri; Ferinaldi (Hira Institute, 2025)
Low data literacy and statistical data visualization skills remain a problem among beginners, especially in Merangin Regency. Statistical data provided by the Central Statistics Agency (CSA) is generally presented in the form of tables of numbers that are difficult to understand for people without a background in statistics. This community service activity aims to improve data literacy and statistical data visualization skills through the use of digital technology. The activity was carried out using a participatory approach through training and mentoring at the Merangin Regency BPS Office Hall, with participants consisting of students and the general public. The implementation of the activity included the preparation, training, mentoring, and evaluation stages. The material provided covered an introduction to basic statistical data concepts and data visualization practices using Microsoft Excel and Google Data Studio. Evaluation was conducted through observation and questionnaires. The results of the activity show that more than 80% of participants experienced an increase in their understanding of basic statistical concepts and were able to create simple data visualizations in the form of bar charts, pie charts, and line graphs using local statistical data. The assistance provided helped participants overcome technical obstacles in using digital applications. This activity had a positive impact on improving the data literacy of novice communities and encouraged more effective use of statistical data in data-based decision making at the local level